The Integration of Local Wisdom Values and the Improvement of Santri’s Tolerance: A Study on the Pesantren in East Kalimantan - Khojir, Khojir; Zurqoni, Zurqoni; Sudadi, Sudadi; Afendi, Achmad Ruslan (Ulumuna, 2025)
Pesantren has a significant influence on the development of santris’ personality and cultural tolerance. However, the flow of globalization through digital media and the influence of foreign cultures shake santris' preferences and threatened local wisdom. This paper aims to analyze the integration between local policies in halaqah knowledge acquisition and its advancement of the cultural tolerance of santri. With an interpretive research paradigm, this study employs the case study method and focuses on several Pesantrens in Benua Etam, East Kalimantan. The data were obtained through interviews with informants, including pesantren leaders, ustadz, and santri and observations, and documentation. Validation techniques include source triangulation, member checking, trail auditing, and peer debriefing. This study reveals that the incorporation of indigenous knowledge within the framework of halaqah was a significant factor in the study's outcomes, significantly increasing the tolerance of santris, as reflected by a 50.92% increase in participation in local traditions and higher acceptance of cultural diversity. Santri who follow culture-based halaqahs demonstrate openness, recognition of community traditions, and the ability to bridge cultural differences without compromising Islamic principles. This study concludes that the culturally based halaqah model is effective in maintaining an inclusive Islamic identity while facing the challenges of globalization.